Explaining the problems of tourism in Kundasang, Sabah: the strengths and limitations of the positivist perspective - Ramzah Dambul; Amriah Buang (Faculty of Social Sciences and Humanities, UKM,Bangi, 2008)
This paper is basically an attempt to explicate the problematique of tourism in Kundasang (Sabah) from the epistemological standpoint of positivism. The objectives are (i) to present several empirical aspects of the problems besetting the tourism industry in the study area, (ii) to account for those problems or shortcomings from the positivist perspective, and (iii) to show how more meaningful explanations could and should be obtained from epistemological perspectives other than positivism. It is found that the strength of the positivist perspective is in the empirical identification of three main factors that have led to the failure of the tourist industry as a development catalyst for Kundasang, namely the lethargic growth of the urban centre, leakages of incomes from the area, and the low level of positive attitudes and behaviour on the part of the local populace.In contrast, the positivist perspective is found to be unable to frame and answer two fundamental critical questions that underline the problems and failure of the Kundasang tourist industry, viz: (a) why did the investment that flowed into Kundasang fail to generate the economic multiplier and spread effects at the local level?; and (b) why did the significant presence of migrant foreign workers not contribute to the growth of the retail and urban services in Kundasang? The paper concludes that answering such questions necessitates the application of non-positivist epistemologies